2006
DOI: 10.1074/jbc.m602119200
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous Polyposis Coli Control of C-terminal Binding Protein-1 Stability Regulates Expression of Intestinal Retinol Dehydrogenases

Abstract: Mutations in the human adenomatous polyposis coli (APC) gene are thought to initiate colorectal tumorigenesis. The tumor suppressor function of APC is attributed primarily to its ability to regulate the WNT pathway by targeting the destruction of ␤-catenin. We report here a novel role for APC in regulating degradation of the transcriptional co-repressor C-terminalbinding protein-1 (CtBP1) through a proteasome-dependent process. Further, CtBP1 suppresses the expression of intestinal retinol dehydrogenases, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…Additional studies indicated that APC control of retinoic acid biosynthesis occurs through the transcriptional regulator CtBP-1 and that this control is independent of ␤-catenin (39,40). Although the regulation of retinoic acid biosynthesis appears independent of the actions of ␤-catenin, the converse may not hold true.…”
Section: Discussionmentioning
confidence: 88%
“…Additional studies indicated that APC control of retinoic acid biosynthesis occurs through the transcriptional regulator CtBP-1 and that this control is independent of ␤-catenin (39,40). Although the regulation of retinoic acid biosynthesis appears independent of the actions of ␤-catenin, the converse may not hold true.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, mouse Dhrs9 has not been knocked out, but the zebrafish ortholog of Dhrs9 contributes to atRA production that supports gut development (8). In mammalian cells, Dhrs9 seems to function as a tumor suppressor, consistent with its poor expression in colon cancer cell lines accompanied by insubstantial atRA biosynthesis, relative to normal colon cells (9). In the frog, overexpression of Rdhe2 produces posteriorization defects, similar to those caused by atRA toxicity, whereas substantial knock-down causes embryonic lethality (10).…”
mentioning
confidence: 99%
“…Recent studies have found increased levels of CtBP1 protein in adenomas from FAP patients. 24,25 CtBP is regulated at the post-translational level by several tumors suppressors, 19,23,24 but there has been no systematic examination of CtBP1 and CtBP2 protein expression in human tumors. Since the cellular CtBP antagonist and tumor suppressor ARF is silenced due to methylation in ~22-38% of colon cancers, 34 a series of 69 resected colon cancer specimens were analyzed for tumor-specific CtBP expression levels, to probe whether CtBP overexpression occurs in human tumors and especially in those tumors lacking ARF.…”
Section: Transformation Of P19mentioning
confidence: 99%
“…The adenomatous polyposis coli tumor suppressor (APC) targets CtBP for degradation, and inactivation of this APC activity may be a necessary step in colonic adenoma formation. 24,25 Finally, the tumor suppressor ARF can also downregulate CtBP by targeting it for proteasomal degradation, inducing Bik-dependent apoptosis. 19,26 ARF is also capable of blocking CtBP-mediated repression of PTEN and by doing so, ARF can inhibit CtBP-dependent hypoxia-induced, cancer cell migration.…”
Section: Introductionmentioning
confidence: 99%